La relocalisation des terres agricoles en ville : des sols et des paysages à (re)connaître - Claire Aragau (Projets de Paysage)
Environmental injunctions, new expectations regarding food supply, and the search for outlets for producers are contributing to a redefinition of the role of agriculture in the city. Based on case studies in the region of the Ile-de-France, in Paris and its outskirts, the article examines the way in which the link between urbanised land and agricultural uses is established and (re)constructed. While urban agriculture principally involves above-ground production systems, the aim is to understand how the relationship to the land and the urban soil can be re-established in all its dimensions, including land ownership and pedological and agronomic qualities, for it to produce food. This redefinition of the relationship between the city and agriculture via the soil and the open land radically impacts the morphologies and spatial arrangements of a whole range of landscapes that may be described as agri-urban. Their aesthetics are marked by technical elements, adjustments and an unsustainable aspect which all relate to the difficulties of using the soil for agricultural purposes in an urban context.